Gossica M-21, nueva variedad de algodón de fibra media para la Costa Atlántica. - Mendoza Olivella, A.M.; Aramendiz Tatis, H.; Murgas A, R. (Federación Nacional de Algodoneros, 2018)
Algodón-Gossypium herbaceum